Lion Air Baggage Cases: Many Cases of Damage to Passenger Suitcases - Okta Alfiana, Aini; Azzahra, Mahadewi; Fadillah, Nurul (Educationist: Journal of Educational and Cultural Studies, 2022)
This paper is based on the author's observations about the number of cases of baggage damage that occurred in one airline. Regarding baggage damage done by the airline to passengers, this of course causes losses for the passengers, both material and immaterial losses, because passengers who have ordered and purchased tickets at a certain price and with a specific purpose have fulfilled the obligation to store their luggage with the third party. airline but in practice, it is not what is expected. This study aims to explain the form of response from related parties in this case PT. Lion Air Group is an airline with baggage damage cases that occur quite often and make a bad reputation. The research method used is the collection of information or data through systematic observation and recording of phenomena for observation. From the results of this study, the author will examine as well as show how in responding to cases of baggage problems at airports, and how airlines handle Online Reputation Management to improve their existing reputation. In this case, the company's response to customer complaints will be analyzed.